Evaluating Proximal Femur Morphometry by Radiography and Its Association with Bone Mineral Density: Insights from a Comprehensive Cross-Sectional Analysis - Nayak, Lopamudra; Baisakh, Pratima; Panda, Sitansu Kumar; Panda, Dhiren Kumar (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
Background: The morphometry of the proximal femur, including hip axis length (HAL), femoral neck axis length (FNAL), and femoral neck shaft angle (FNSA), plays a crucial role in assessing fracture risk. This study aims to elucidate the association between proximal femur morphometry and bone mineral density (BMD), considering various demographic and physiological factors. Methods: In this cross-sectional study, we analyzed 168 patients using dual-energy X-ray absorptiometry (DEXA) scans to measure HAL, FNAL, FNSA, and FN-BMD. We employed a LUNAR XR scanner for precise BMD measurement, ensuring the integrity and comparability of data. Results: Our analysis revealed significant negative correlations between FN-BMD and HAL (r=-0.791), FNAL(r=-0.734), and FNSA(r=-0.713), underscoring the predictive value of proximal femur morphometry on BMD. These findings highlight the potential of morphometric parameters in enhancing fracture risk prediction models. Conclusion: This study establishes a significant association between proximal femur morphometry and BMD, contributing valuable insights to the field of osteoporosis research and fracture risk assessment. Further research is recommended to explore the clinical applications of these findings in personalized medicine.